Community Education on Low-Sugar Healthy Meal Preparation for Housewives - Nurani Rahmania (STAI Miftahul ULa Nganjuk, 2025)
Excessive sugar consumption is a significant public health concern linked to the rising prevalence of non-communicable diseases. Housewives, as primary family food managers, play a crucial role in determining dietary patterns. This community service program aimed to empower housewives in Bangle Village, Lengkong District, through education on low-sugar healthy meal preparation. The program employed the Asset-Based Community Development (ABCD) approach, focusing on identifying and mobilizing existing community assets rather than addressing deficits. Methods included asset mapping, interactive nutrition workshops, and participatory cooking practices. The initial mapping revealed key assets: the culinary skills of housewives, the structured network of the PKK (Family Welfare Empowerment), and the availability of local ingredients. The intervention resulted in a significant increase in participants' knowledge, with average pretest and post-test scores rising from 52.4 to 85.6. Furthermore, the program successfully mobilized these assets, as observed in the practical sessions where participants modified traditional recipes to reduce sugar content. More importantly, the ABCD approach fostered sustainable community ownership, leading to the formation of the